Pengembangan Bio-Baterai dengan Elektrolit Padat Berbasis Tepung Tapioka dan Serbuk Kulit Udang Air Laut Sebagai Sumber Ion - Wati, Rosita; Saputra, Edi; Iswan, Joni; Rahman, Dui Yanto; Sulistyowati, Rita (PPSDP Undergraduate Journal of Educational Sciences, 2025)
Bio-batteries offer a potential solution as an alternative to conventional batteries that are not environmentally friendly by utilizing organic and readily available materials, such as shrimp shell powder and seawater. The purpose of this study is to determine the optimal composition of shrimp shell powder and seawater that produces maximum current and voltage. Gafit sheets are used as anodes and aluminum sheets as cathodes. Shrimp shell powder with a mass variation of 2-10 g is dissolved in 20 ml of mineral water (Aqua) using a magnetic stirrer for 10 minutes, then 35 g of tapioca flour is added gradually until it forms a solid electrolyte. This electrolyte is placed between the sheets of gafit and aluminum. The optimal composition of shrimp shell powder is combined with seawater (1-5 ml) to increase current and voltage. The results showed that the bio-battery that used only shrimp shell powder solution produced a maximum current of 0.68 mA and a voltage of 0.803 V with an optimum mass of 6 g. The combination of shrimp shell powder and seawater produces a current of 2.02 mA and a voltage of 0.858 V with an optimum volume of 3 ml of seawater. This research shows great potential for further development because the method is simple and the materials used are cheap and environmentally friendly.